Prediction of Bleeding via Simulation of Hydrodynamics in Centrifugal Partition Chromatography - Felix Buthmann; Sophia Volpert; Jörg Koop; Gerhard Schembecker (Separations, 2024)
Centrifugal Partition Chromatography (CPC) utilizes a two-phase liquid–liquid system as mobile and stationary phases. During operation, the latter continuously drains out of the rotor, despite it being in fact stationary, leading to decreasing separation efficiency over time, a phenomenon still poorly understood today because neither simulations nor extensive experimental investigations have addressed this so-called bleeding. With the model presented in this study, the underlying hydrodynamics are discussed in detail. This model can simulate bleeding over 60 s and is verified experimentally for different operating points (volumetric flow rates of 5, 12, and 20 mL⋅min−1) of the Centrifugal Partition Chromatograph utilizing an aqueous–organic phase system. We simulated two interconnected chambers at the rotor inlet and analyzed the loss of the stationary phase over time. The results of the simulated second chamber are closely aligned with the experimental validation results. Thus, the prediction of bleeding utilizing the simulation of hydrodynamics was successful. Moreover, we highlighted the benefits of the two-chamber setup modeled in this study compared to single-chamber models.